Особливості системи вентиляції для усунення вологи та шкідливих речовин у приміщеннях - Панова, А. С. (ХНУРЕ, 2019)
The paper discusses the demand control ventilation that will make it possible to improve ventilation in buildings. This system is a very efficient, smart technology that measures the environmental conditions and provides the level of ventilation required to achieve a more comfortable healthy environment. The demand control ventilation is based on using carbon dioxide, noise, humidity and temperature sensors and providing with the right amount of fresh air, when they need it, where this is useful. An activity which emits indoor air pollution such as the release of odorous metabolic compounds, excessive increase in humidity, breathing, sweating, generates a need for a greater ventilation to remove the pollution quickly.
Keywords: адаптивні системи вентиляції; цифрові датчики